Palveluyrittäjyys kasvaa nopeimmin ja työllistää eniten - Petri Rouvinen; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2004)
– This report studies start-ups and entrepreneurship particularly in services. The report is largely based on a survey targeted to Finnish businesses established in October 2003. The Finnish total entrepreneurial activity is relatively low in international comparison. Furthermore, established firms have on average relatively modest growth ambitions. In Finland entrepreneurship in services has grown the fastest and employs the most. Service and female entrepreneurship seem to be on the increase - the survey suggests that three fourths of starting entrepreneurs are in services and four in ten are females. Both are one tenth higher than the corresponding fractions among the current entrepreneurs. It seems that start-ups are unlikely to solve the aching unemployment problem in Finland. Public finance and other services seem to reach starting entrepreneurs poorly as compared to existing small and medium-sized enterprises. There is some indication that entrepreneurial activity is higher among the younger age-groups in the Finnish working-age population.
Keywords: 330; Entrepreneurs; entrepreneurship; services; small firms; entry